A clinical audit: dental treatment needs and treatment received by 12 and 15 year old children who attended the Wits Dental Hospital during the period: January 2006 to December 2010 - Bagus, Tashnim (My University, 2013)
A Clinical Audit: Dental Treatment Needs and Treatment Received by 12 and 15 year old children who attended the WITS Dental Hospital during the period January 2006 to December 2010. Background The majority of children and adults are affected by dental caries and its sequelae in South Africa. Children, from lower socioeconomic backgrounds in particular, continue to experience a high burden of dental caries. Objectives - To determine the number and profile of 12 – year – old and of 15 – year – old patients who attended the Wits Dental Hospital during the period of January 2006 to December 2010. - To determine the dental treatment needs of the two index age groups, including caries prevalence and the teeth affected by caries. - To determine the treatment received during this period. - To determine the time taken to complete the treatment needed and the number of patient visits required. - To determine the obstacles to receiving or completing the prescribed treatment. xii | P a g e Subjects and Methods The study was based on a retrospective review of the dental treatment records of 12 – year – old and 15 – year – old children attending the WITS Dental Hospital during the period January 2006 to December 2010. The study was based on children treated in the dental chair and did not include children treated under general anaesthetic. A total of 143 dental treatment records were retrieved , but only 62% (89) of the records met the specified study requirements – (39 for 12 yr olds and 50 for 15 yr olds). Extracted data was recorded by the researcher onto specifically – formulated data capture sheets. Processing and analysis of data was carried out with SPSS for Windows, Version 13 . Chi – square tables were constructed for comparison of proportional distributions. Exact and Monte Carlo test statistics were calculated to identify significant relationships. Results The mean DMFT for the 12 – year – old age group was 3.0 . The DT accounted for 76.6% of the DMFT , the MT for 23.33% and the FT was nil. The mean DMFT for the 15 – year – old age group was 3.8. The DT accounted for 92.1% of the DMFT , the MT for less than 10% and the FT was nil. There is an increase in dental caries from 12 – year – old to 15 – year – old patients. Carious teeth are left untreated. Restorative dental treatment levels are low. Low levels of completed treatment plans noted. Conclusion The rise in dental caries from the 12 – year – old group to the 15 – year – old group, together with high levels of untreated caries and low levels of restorative dental xiii | P a g e treatment indicate the need to improve the oral health of school children. Evidence – based oral health prevention and promotion strategies must guide oral health policy planning, so that supportive environments are created and sustained to facilitate healthy choices and maintain optimal oral health.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science (Dentistry) In the Department of Paediatric and Restorative Dentistry School of Oral Health Sciences Faculty of Health Sciences University of the Witwatersrand, Johannesburg
Keywords: Dental Health Services; Dental Clinics; Dental Care--in infancy & childhood